A kinetic view of clathrin assembly and endocytic cargo sorting. (August 2021) - Wu, Min; Wu, Xudong
Abstract: Specificity and sensitivity in biochemical reactions can be achieved through regulation of equilibrium binding affinity or through proofreading mechanisms that allow for the dissociation of unwanted intermediates. In this essay, we aim to provide our perspectives on how the concept of kinetic proofreading might apply in the context of cargo sorting in clathrin-mediated endocytosis.